The presentation of graphs in annual reports: The case of the KLSE corporate awards winners - Abd Wahab, Muhammad Syahir; Mat Samsudin, Mohd Amir (Universiti Utara Malaysia, 2005)
Misleading graphs could be the result of annual report preparers’ ignorance, carelessness, or intention to use impression management. The graphs impair the communication effectiveness, even though this has not been tested empirically.Unfortunately, the use of the graphs appears to be widespread due to many parties (for example users, auditors, and preparers of annual reports) not familiar with the potential abuses of construction standards.The aim of this study is to determine whether annual reports by the Kuala Lumpur Stock Exchange (KLSE, now known as Bursa Malaysia) Corporate Awards winners contain inconsistent graphs by assessing graph accuracy based on the guidelines for good graphics as set forth in previous literature and graph discrepancy index (GDI), also known as graph measurement distortion (part of impression management).The methodology used is an adaptation of the graphical guidelines developed by Schmid and Schmid (1979), Tufte (1983), Jarett and Babad (1988), Canadian Institute of Certified Accountant (CICA) (1993), Jarett (1993), and subsequently applied by Frownfelter-Lohrke and Fulkerson (2001).The GDI was calculated using a variant of Tufte’s (1983) lie factor.As far as we are aware, this is the first study in Malaysia to investigate the graph presentation in annual reports of companies that had received awards for their annual reports.It was discovered that 95% of companies in our sample used graphs, which included most of the key financial variables (KFVs) graphs, that exhibited more material overstatement (mean +61.78%) than understatement distortion (mean -45.79%), and many graphs conform to the suggested graph guidelines.